2007
DOI: 10.1002/jnr.21477
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of brain metabolism by very low concentrations of the commonly used drug delivery vehicle dimethyl sulfoxide (DMSO)

Abstract: Dimethyl sulfoxide (DMSO) has long been used in studies as a vehicle to enhance the solubility and transport of ligands in biological systems. The effects of this drug on the outcomes of such studies are still unclear, with concentrations of DMSO reported as "safe" varying considerably. In the present work, we investigated the effects of very low concentrations of DMSO on the brain metabolism of [3-(13)C]pyruvate and D-[1-(13)C]glucose using (1)H/(13)C NMR spectroscopy and a guinea pig cortical brain slice mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 37 publications
0
35
0
2
Order By: Relevance
“…This suggested that AMPA activation is specifically targeting a pool of lactate which is not rapidly accessible to 13 C from glucose. Evidence for such as pool has been presented previously [41] and our own experiments with [3-13 C]pyruvate as a substrate have indicated that more pools are labelled with this substrate than with [1-13 C]-glucose (e.g., [20,42,43]). …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This suggested that AMPA activation is specifically targeting a pool of lactate which is not rapidly accessible to 13 C from glucose. Evidence for such as pool has been presented previously [41] and our own experiments with [3-13 C]pyruvate as a substrate have indicated that more pools are labelled with this substrate than with [1-13 C]-glucose (e.g., [20,42,43]). …”
Section: Discussionmentioning
confidence: 74%
“…AR-C122982 is not soluble in water so it was dissolved initially in DMSO. It is known that DMSO has separate effects on metabolism, which mostly are limited to increasing the metabolic rate, most probably through interference with ATP-requiring reactions [20]. DMSO was added to all control experiments to the same concentration as that used in the experiments containing AR-C122982.…”
Section: Inhibition Of Lactate Transportmentioning
confidence: 99%
“…At the very least, there may be an interaction between the DMSO and acetazolamide as the AUC analysis showed that acetazolamide treatment significantly increase hippocampal glucose levels. The effects of DMSO on brain metabolism has been implied for several years; early work indicated that the application of DMSO to brain slices increases glucose consumption (Ghosh et al, 1976) and in vitro administration of DMSO appears to cause more varied dose-dependent effects on glucose metabolism in brain slices from guinea pigs (Nasrallah et al, 2008). Comparing our results to those of these other groups creates a complex picture with low concentrations of DMSO administered directly to brain tissue causing rapid changes in glucose metabolism in contrast to our findings where high concentrations of DMSO administered intraperitoneally caused a delayed but long-lasting increase in glucose concentration, perhaps reflecting a decrease in glucose consumption over longer time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Idiosyncratic mechanisms, a predisposing genetic background and a direct effect of DMSO on neural cell metabolism have also been hypothesized. [5][6][7]9 Whether the occurrence of neurotoxicity is related to the amount of DMSO infused (maximal recommended dose is 1000 mg/kg or 10 ml/kg of a 10% solution) and/or to infusion rate also remains controversial. 7 Our patient developed symptoms after receiving only 10.5 ml of DMSO at a low infusion rate, suggesting that patient-related factors might have also contributed to the development of neurotoxicity.…”
mentioning
confidence: 99%
“…In our case, at least three factors might have concurred to the neurologic event by sensitizing brain tissues to direct DMSO toxicity. 9 CNS lymphoma involvement might have altered brain cellular milieu, whereas treatment with intrathecal long-acting cytarabine and exposure to high-dose cytarabine (12 g/m 2 over 3 days) could have produced preceding neural cells damage. The short-time interval elapsed from the last intrathecal therapy (76 days), systemic high-dose cytarabine (30 days) and PBSC infusion may have facilitated the neurotoxic action of DMSO.…”
mentioning
confidence: 99%